La suspensión de labores por caso fortuito y fuerza mayor: análisis legal y casuístico - Lora Álvarez, Germán (Pontificia Universidad Católica del Perú, 2016)
This article addresses the theme referred to the remedies of the suspension of work by reason of fortuitous event or force majeure. Through an analysis of the current legislation in the subject and administrative precedents, the author examines how this regulation is applied, and how this mechanism allows or not the labour continuity. By recognizing labour continuity as the foundation of the suspension of work by reason of fortuitous event and force majeure, the author concludes in the need for legal mechanisms to enable the employment relationship flexibilization.

El presente artículo aborda la temática referida a la suspensión de labores por caso fortuito o fuerza mayor. Realizando un análisis sobre la legislación vigente en la materia y precedentes administrativos, el autor examina cómo es que la regulación se aplica, y cómo este mecanismo permite o no la continuidad laboral. Reconociendo la continuidad laboral como fundamento de la suspensión por caso fortuito y fuerza mayor, el autor concluye en la necesidad de mecanismos legales que permitan la flexibilización de la relación laboral.
Suspension of work by reason of fortuitous event and force majeure: legal and case-by-case analysis
Keywords: Employment Relationship; Labour Continuity; Fortuitous Event; Force Majeure; Suspension Of Employment Contract; Administrative Precedent; Relación Laboral; Continuidad Laboral; Caso Fortuito; Fuerza Mayor; Suspensión del Contrato de Trabajo; Precedente Administrativo; https://purl.org/pe-repo/ocde/ford#5.05.00